THERMOLUMINESCENT DATING OF THE LATE BRONZE AND EARLY IRON AGE POTTERY ON SITES IN KŁYŻÓW AND JAROSŁAW (SE POLAND) - Czopek, Sylwester; Kusiak, Jarosław; Trybała-Zawiślak, Katarzyna (Springer, 2013)
The absolute chronology of Late Bronze and Early Iron Ages in Polish territories is a result of long-term and complex research. Here, we have investigated the absolute dating of two sites, namely Kłyżów, a cemetery of the Tarnobrzeg Lusatian culture, and Jarosław, a settlement spanning from the late phase of the former to Pomeranian culture, possibly with Jastorf elements. Having been spurred by promising results of thermoluminescence (TL) dating of medieval and Przeworsk materi-als, we have employed it in those situations, where no other chronometric methods seem to be effi-cient. TL dating has been combined with typological analysis of the dated pottery and, partially, with radiocarbon method. Albeit the produced TL dates do not represent the level of sought-for fine chron-ological resolution, they indicate the temporal trends and corroborate the typological research. Our study has shown the potential of TL dating for periods with plateaus on 14C calibration curve. We also have dealt with unexpected TL ages and suggested some solutions of the problem. Finally, we have demonstrated that the condition sine qua non for archaeological interpretation of TL dates is a thor-ough stylistic-chronological analysis of dated pottery and clear understanding of relations between chronometric dates and the archaeological event to be dated.
Keywords: TL dating; Early Iron Age; Tarnobrzeg Lusatian culture; Pomeranian culture